Combination of acid washing and torrefaction on Co-production of syngas and phenoli-riched bio-oil via low-temperature catalytic pyrolysis. (1st November 2020) - Su, Yinhai; Zhang, Shuping; Liu, Lingqin; Xu, Dan; Qi, Penggang; Xiong, Yuanquan
Abstract: This study was targeted on investigating the facilitations of the combined pretreatment of acid washing and torrefaction on the co-production of syngas and phenols-rich bio-oil. Comparison of raw and modified samples indicated that combined pretreatments not only effectively removed the bulk of alkali and alkaline earth metals but also improved the fuel properties by decomposing unstable hemicellulose. Then, via the catalytic reforming of activated carbon catalyst, CO-rich syngas and phenols-rich bio-oil were obtained simultaneously. The optimal products was acquired from the acid-washed sample which torrefied at 240 °C (labeled as AT240). This syngas contained the maximal CO concentration of 61.86%, and its yield reached 174.34 mL/g. In bio-oil, relative content of phenolic compounds was 91.44%, in which the phenol occupied 71.72%. Quantitative analysis revealed the quantity of phenol in AT240 was 1.74 times of raw bio-oil. Furthermore, mechanism of combined pretreatment on catalytic co-production of syngas and phenols was proposed and discussed in this paper Highlights: Combined pretreatments and catalytic pyrolysis were integrated to upgrade products. The maximal CO concentration in syngas was 61.86 vol%. The optimum phenol content in bio-oil was 71.72%. Mechanisms of phenol and syngas co-generation was discussed.